2012
DOI: 10.1111/apa.12059
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbial profiles in extremely preterm infants with and without necrotizing enterocolitis

Abstract: No significant differences in the composition of intestinal microbiota of patients developing NEC were detected; however, some findings need to be scrutinized in subsequent studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 33 publications
(76 reference statements)
6
73
0
Order By: Relevance
“…infants who developed NEC had lower Firmicutes and higher Proteobacteria in their intestinal microbiome (2,5), but others claim that there is no difference in the composition of intestinal microbiota in those who develop NEC (14). Wang et al (2) have reported the most striking difference in intestinal microbiota between NEC and non-NEC infants, but fecal samples were obtained after the diagnosis of NEC had been made.…”
Section: Antibiotics and The Preterm Microbiomementioning
confidence: 99%
“…infants who developed NEC had lower Firmicutes and higher Proteobacteria in their intestinal microbiome (2,5), but others claim that there is no difference in the composition of intestinal microbiota in those who develop NEC (14). Wang et al (2) have reported the most striking difference in intestinal microbiota between NEC and non-NEC infants, but fecal samples were obtained after the diagnosis of NEC had been made.…”
Section: Antibiotics and The Preterm Microbiomementioning
confidence: 99%
“…There are conflicting reports in the literature, with some studies showing no association of the gut microbiota with incidence of NEC [3], whereas others studies identify particular taxa (i.e. Klebsiella; Clostridium) correlated with an increased risk of disease [4].…”
Section: Main Articlementioning
confidence: 99%
“…Prospective studies that analyzed stool samples before the onset of NEC suggest that the disease is associated with reduced microbial diversity that could accentuate the impact of single dominant species of microbes. Such dysbiosis is promoted by the widespread use of antibiotics in the neonatal intensive care unit setting (26,27). The results of meta-analyses of prospective randomized clinical trials related to the role of probiotics in preventing NEC also support the importance of the gut microbiota in the pathogenesis of disease (28).…”
Section: Current Status Of Knowledgementioning
confidence: 97%
“…Full-term breastfed neonates are colonized with a number of bacterial species, including Bifidobacteria, Lactobacilli, Bacteroidetes, Proteobacteria, and Streptococci (43), all of which contribute to gut function. VLBW preterm infants possess a greater number of pathogenic microbes, such as Escherichia coli and Clostridium difficile, despite being fed breast milk (27).…”
Section: Management Strategiesmentioning
confidence: 99%